2018
DOI: 10.1097/md.0000000000011358
|View full text |Cite
|
Sign up to set email alerts
|

The influence of strain due to individual risk factors and social risk factors on depressive symptoms and suicidality-a population-based study in Korean adults

Abstract: Suicide is the outcome of the interaction of biological, personal, and social risk factors. The purpose of this study was to verify the effects of strain due to individual risk factors and social risk factors on suicidality, and the mediating effect of depressive symptoms in relationship between strain related to individual risk factors and social risk factors and suicidality. The data from sociopsychological anxiety survey of Korea society conducted by the Korea Institute for Health and Social Affairs in 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, several limitations need to be addressed. First, some confounding factors of the association between depression and CVD, such as income, social support, isolation, and joblessness, 58,59 were not adjusted in this study. Second, similar to other studies, 60,61 for logistical reasons, the diagnosis of CVD was self-reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, several limitations need to be addressed. First, some confounding factors of the association between depression and CVD, such as income, social support, isolation, and joblessness, 58,59 were not adjusted in this study. Second, similar to other studies, 60,61 for logistical reasons, the diagnosis of CVD was self-reported.…”
Section: Discussionmentioning
confidence: 99%